Unilateral subthalamotomy in Parkinson's disease: Cognitive, psychiatric and neuroimaging changes. (September 2017) - Obeso, Ignacio; Casabona, Enrique; Rodríguez-Rojas, Rafael; Bringas, Maria Luisa; Macías, Raúl; Pavón, Nancy; Obeso, Jose A.; Jahanshahi, Marjan
Abstract: Unilateral subthalamotomy is an effective treatment for the cardinal motor features of Parkinson's disease (PD). However, non-motor changes possibly associated with right or left subthalamotomy remain unknown. Our aim was to assess cognitive, psychiatric and neuroimaging changes after treatment with unilateral subthalamotomy. Fourteen medicated patients with PD were evaluated before and after (mean 6 months after operation) unilateral subthalamotomy (5 right, 9 left). In addition to motor assessments, cognitive (global cognition and executive functions), psychiatric (apathy, depression, anxiety, mania, hypo- and hyperdopaminergic behaviours, impulsivity), quality of life evaluations and volume of lesions were obtained. After surgery, significant improvement of motor signs was observed. Unilateral subthalamotomy improved general cognitive status, but left subthalamotomy reduced semantic verbal fluency compared to the pre-operative state. Depression and quality of life were improved with both right and left subthalamotomy. However, hyper-emotionality was present after surgery and right subthalamotomy increased impulsivity and disinhibition (on NeuroPsychiatric Inventory and Ardouin Scale for Behaviour in PD), a result linked to larger lesion volumes. We conclude that unilateral subthalamotomy is effective for treating the cardinal motor features of PD and improves mood. Right subthalamotomy is associated with greater risk of impulsivity and disinhibition, while left subthalamotomy induces further impairment of semantic verbal fluency.